2018
DOI: 10.18388/abp.2018_2565
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of long-chain polyunsaturated fatty acids in phenylketonuria: a cross-sectional study

Abstract: The etiology of altered blood fatty acid (FA) profile in phenylketonuria (PKU) is understood only partially. We aimed to determine whether FAs deficiency is dependent on the diet or metabolic disturbances. The study comprised 40 PKU patients (20 female, 20 male; aged 11 to 35 years; 12 children and 28 adults) and 40 healthy subjects (HS; 20 female, 20 male, aged 18 to 33 years). We assessed the profile of FAs (gas chromatography/mass spectrometry) and analyzed the 72-hour dietary recalls. The amount of C14:0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…LCPUFAs have been found to be decreased in systematic review and meta-analysis of studies in PKU, likely secondary to dietary restriction and possibly metabolic changes, though the latter is only partially understood (174, 175). The addition of omega-3 docosahexaenoic acid (DHA) to the diet of children with PKU has been shown to increase central nervous system processing speed (as measured by visual evoked potentials) as well as motor and coordination skills, suggesting DHA is an essential part of the treatment of PKU (176).…”
Section: Case Vignettesmentioning
confidence: 99%
“…LCPUFAs have been found to be decreased in systematic review and meta-analysis of studies in PKU, likely secondary to dietary restriction and possibly metabolic changes, though the latter is only partially understood (174, 175). The addition of omega-3 docosahexaenoic acid (DHA) to the diet of children with PKU has been shown to increase central nervous system processing speed (as measured by visual evoked potentials) as well as motor and coordination skills, suggesting DHA is an essential part of the treatment of PKU (176).…”
Section: Case Vignettesmentioning
confidence: 99%
“…Interestingly, patients/caregivers reported more problems with low-Phe products than with Phe-free formulas, but it was less difficult for most patients to adhere to the diet during the lockdown than before. Assuming that this was the reality, that is, due to objective or subjective causes, e.g., pandemic-related stress and not exclusively the patients’ feelings, it could have impacted their diet and deteriorated problems related to vitamin and mineral intake already observed in the pre-pandemic period [ 13 , 14 , 15 , 16 , 17 ]. Moreover, these issues together with general changes in food consumption observed during the pandemic could have influenced energy and metabolic balance, increasing overweight and obesity problems observed in patients with PKU [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenylketonuria (PKU) is the most prevalent inborn error in amino acid metabolism. PKU is characterized by an impaired activity of the enzyme phenylalanine hydroxylase (PAH), resulting in a complete or partial inability of the enzyme to convert l -phenylalanine (Phe) to l -tyrosine. Deficiency of the PAH enzyme results in increased levels of Phe in the blood (hyperphenylalaninemia). The accumulation of Phe can lead to intellectual impairment, microcephaly, seizures, and motor deficits. ,, Early diagnosis through neonatal screening and rapid therapeutic implementation are essential to prevent these possible complications . The therapeutic approach for PKU is based on a lifelong Phe-restricted diet, with a low intake of natural proteins …”
Section: Introductionmentioning
confidence: 99%
“…The existing literature is ambiguous about the prevalence of long-chain PUFA deficiency in patients with PKU. However, some studies have shown a significant decrease in important PUFA, such as docosahexaenoic acid (DHA, 22:6 n – 3), eicosapentaenoic acid (EPA, 20:5 n – 3) and arachidonic acid (AA, 20:4 n – 6), in patients with PKU who maintained a Phe-restricted diet (with no information available on PUFA supplementation). These reduced levels have been associated with dietary restrictions, as PKU patients do not consume foods of animal origin rich in PUFA. ,, The low dietary intake of long-chain PUFA is thought to be the main cause of the decrease in the levels of DHA, EPA and AA, as their endogenous synthesis is very low. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation